Risk Factors Influencing Seeking Emergency Medical Service in Urban and Rural China Among Participants With a Previous Transient Ischemic Attack - Yuan, Jing; Shan, Guang-Liang; Li, Sheng-De; Gao, Chun-Peng; Cui, Li-Ying; Peng, Bin (Frontiers in Neurology, 2021)
Objective: It is critical to identify factors that significantly impede the correct action of calling emergency medical service (EMS) in the high-risk population with a previous history of transient ischemic attack (TIA) and further explore the urban-rural difference in China. Methods: Participants with previous TIA from the China National Stroke Screening Survey and its branch study (FAST-RIGHT) were interviewed cross-sectionally (n=2,036). The associations between the outcome measure of not calling EMS and multiple potential risk factors were examined, including demographic information, live (or not) with families, medical insurance type, urban or rural residence, awareness of stroke symptoms, annual personal income, presence of cardiovascular disease or risk factors, and stroke history in family members or friends. The sample was further stratified to explore the urban-rural difference by their residency. Results: The proportion of not calling EMS was 36.8% among all participants with previous TIA, and that was 21.7% and 48.4% among urban and rural participants, respectively. Among rural participants, risk factors that were significantly associated with not calling EMS including primary school education (OR 2.50, 95% CI 1.89-3.33), living with family (OR 2.09, 95% CI 1.33-3.36), unaware stroke symptoms (OR 2.60, 95% CI 1.81-3.78), and low-income (OR 1.57, 95% CI 1.19-2.07). Among urban participants, only low-income was significantly associated with increased risk of not calling EMS (OR 1.74, 95% CI 1.10-2.72). Conclusions: Rural residents with previous TIA in China had a higher percentage of not calling EMS. Multiple risk factors have been identified that call for targeted intervention strategies.